como resolvo
(5x+2)² - (3x-4)² =
Soluções para a tarefa
Respondido por
0
Boa noite Demileide!
Solução!
![(5x+2)^{2} -(3x-4)^{2} (5x+2)^{2} -(3x-4)^{2}](https://tex.z-dn.net/?f=%285x%2B2%29%5E%7B2%7D+-%283x-4%29%5E%7B2%7D+)
![(25 x^{2} +10x+10x+4)-(9 x^{2} -12x-12x+16) (25 x^{2} +10x+10x+4)-(9 x^{2} -12x-12x+16)](https://tex.z-dn.net/?f=%2825+x%5E%7B2%7D+%2B10x%2B10x%2B4%29-%289+x%5E%7B2%7D+-12x-12x%2B16%29)
![(25 x^{2} +20x+4)-(9 x^{2} -24x+16) (25 x^{2} +20x+4)-(9 x^{2} -24x+16)](https://tex.z-dn.net/?f=%2825+x%5E%7B2%7D+%2B20x%2B4%29-%289+x%5E%7B2%7D+-24x%2B16%29)
![16 x^{2} +44x-12=0 16 x^{2} +44x-12=0](https://tex.z-dn.net/?f=16+x%5E%7B2%7D+%2B44x-12%3D0)
Aplicando a formula de Bhaskara.
![Formula~~x= \dfrac{-b\pm \sqrt{b^{2}-4.a.c } }{2.a} Formula~~x= \dfrac{-b\pm \sqrt{b^{2}-4.a.c } }{2.a}](https://tex.z-dn.net/?f=Formula%7E%7Ex%3D+%5Cdfrac%7B-b%5Cpm+%5Csqrt%7Bb%5E%7B2%7D-4.a.c+%7D+%7D%7B2.a%7D+)
![x= \dfrac{-44\pm \sqrt{44^{2}-4.16.(-12) } }{2.16} x= \dfrac{-44\pm \sqrt{44^{2}-4.16.(-12) } }{2.16}](https://tex.z-dn.net/?f=x%3D+%5Cdfrac%7B-44%5Cpm+%5Csqrt%7B44%5E%7B2%7D-4.16.%28-12%29+%7D+%7D%7B2.16%7D)
![x= \dfrac{-44\pm \sqrt{1936+768} }{32} x= \dfrac{-44\pm \sqrt{1936+768} }{32}](https://tex.z-dn.net/?f=x%3D+%5Cdfrac%7B-44%5Cpm+%5Csqrt%7B1936%2B768%7D+%7D%7B32%7D)
![x= \dfrac{-44\pm \sqrt{2704} }{32} x= \dfrac{-44\pm \sqrt{2704} }{32}](https://tex.z-dn.net/?f=x%3D+%5Cdfrac%7B-44%5Cpm+%5Csqrt%7B2704%7D+%7D%7B32%7D)
![x= \dfrac{-44\pm 52 }{32} x= \dfrac{-44\pm 52 }{32}](https://tex.z-dn.net/?f=x%3D+%5Cdfrac%7B-44%5Cpm+52+%7D%7B32%7D)
![x_{1} = \dfrac{-44+ 52 }{32}= \dfrac{8}{32} = \dfrac{1}{4} x_{1} = \dfrac{-44+ 52 }{32}= \dfrac{8}{32} = \dfrac{1}{4}](https://tex.z-dn.net/?f=+x_%7B1%7D+%3D+%5Cdfrac%7B-44%2B+52+%7D%7B32%7D%3D+%5Cdfrac%7B8%7D%7B32%7D+%3D+%5Cdfrac%7B1%7D%7B4%7D+)
![x_{2} = \dfrac{-44-52 }{32}= \dfrac{-96}{32} = -3 x_{2} = \dfrac{-44-52 }{32}= \dfrac{-96}{32} = -3](https://tex.z-dn.net/?f=x_%7B2%7D+%3D+%5Cdfrac%7B-44-52+%7D%7B32%7D%3D+%5Cdfrac%7B-96%7D%7B32%7D+%3D+-3)
![\boxed{Resposta: x_{1}= \dfrac{1}{4} ~~ ~~x_{2}=-3 } \boxed{Resposta: x_{1}= \dfrac{1}{4} ~~ ~~x_{2}=-3 }](https://tex.z-dn.net/?f=%5Cboxed%7BResposta%3A+++x_%7B1%7D%3D+%5Cdfrac%7B1%7D%7B4%7D+%7E%7E+%7E%7Ex_%7B2%7D%3D-3++%7D)
Boa noite!
Bons estudos!
Solução!
Aplicando a formula de Bhaskara.
Boa noite!
Bons estudos!
Respondido por
0
(5x+2)² - (3x-4)² =
(5x + 2x2) - (3x-4x4)=
(5x +4) - (3x-8)=
5x +4 - 3x - 8
5x- 3x = 8 - 4
2x = 4
x=4 ÷ pra 2
x=2
Espero ter ajudado :)
(5x + 2x2) - (3x-4x4)=
(5x +4) - (3x-8)=
5x +4 - 3x - 8
5x- 3x = 8 - 4
2x = 4
x=4 ÷ pra 2
x=2
Espero ter ajudado :)
Perguntas interessantes